2017
DOI: 10.4049/jimmunol.1700406
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Dual TCRα Expression Poses an Autoimmune Hazard by Limiting Regulatory T Cell Generation

Abstract: Despite accounting for 10–30% of the T cell population in mice and humans, the role of dual TCR-expressing T cells in immunity remains poorly understood. It has been hypothesized that dual TCR T cells pose an “autoimmune hazard” by allowing self-reactive TCRs to escape thymic selection. We revisited this hypothesis using the NOD murine model of type 1 diabetes (T1D). We bred NOD mice hemizygous at both TCRα and β (TCRα+/− β+/−) loci, rendering them incapable of producing dual TCR T cells. We found that the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Here, strongly self-reactive CD4 + T cells may be clonally deleted or undergo agonist selection to become T reg cells (77). In NOD mice lacking dual TCRa expression (TCRa +/2 ), we observed an increased ratio of T reg cells to SP cells in the thymus and less apoptosis among the signaled CD4SP population, indicating increased T reg commitment and decreased clonal deletion (76). This suggests that dual TCRa-expressing T reg cells should be rare, yet human thymic and peripheral T cells expressing both Va12 and Va2 TCRs were three times as frequent in the CD25 + T reg cellenriched population versus the CD25 2 population, leading to the interpretation that dual TCRa expression may be common in T reg cells (78).…”
Section: Impact Of Dual Tcra Expression On Thymic Selectionmentioning
confidence: 76%
See 2 more Smart Citations
“…Here, strongly self-reactive CD4 + T cells may be clonally deleted or undergo agonist selection to become T reg cells (77). In NOD mice lacking dual TCRa expression (TCRa +/2 ), we observed an increased ratio of T reg cells to SP cells in the thymus and less apoptosis among the signaled CD4SP population, indicating increased T reg commitment and decreased clonal deletion (76). This suggests that dual TCRa-expressing T reg cells should be rare, yet human thymic and peripheral T cells expressing both Va12 and Va2 TCRs were three times as frequent in the CD25 + T reg cellenriched population versus the CD25 2 population, leading to the interpretation that dual TCRa expression may be common in T reg cells (78).…”
Section: Impact Of Dual Tcra Expression On Thymic Selectionmentioning
confidence: 76%
“…Agonist selection. Recently we demonstrated that dual TCR expression might also limit agonist selection of thymic T reg cells (76). Thymocytes that survive positive and negative selection in the cortex migrate to the medulla as single positive (SP) thymocytes where they encounter a new assemblage of self-peptide-MHC.…”
Section: Impact Of Dual Tcra Expression On Thymic Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous examinations of mice genetically deficient for dual TCR expression have not identified overt T cell compartment defects, indicating that dual TCR expression is not absolutely required for T cell development, homeostasis, or function. However, this does not preclude important effects of dual TCR expression on the development, composition, or function of the T cell repertoire.…”
Section: Results and Discusssionmentioning
confidence: 98%
“…The predominant, long-standing theory is that the expression of only one type (specificity) of AgR by T and B cells suppresses autoimmunity by ensuring negative selection of cells expressing a self-reactive receptor (Brady et al, 2010a;Heath and Miller, 1993;Padovan et al, 1993). Consistent with this hypothesis, expression of a second endogenous AgR enables cells bearing a transgenic autoreactive AgR to evade negative selection (Auger et al, 2012;Iliev et al, 1994;Sarukhan et al, 1998;Zal et al, 1996), and biallelic TCRα expression potentiates autoimmune diabetes in the NOD mouse model (Schuldt et al, 2017). Our findings suggest new avenues for investigation.…”
Section: The Broader Impacts Of Vβ Rsss Being a Major Determinant Of mentioning
confidence: 99%